The Lagos Eko Secondary Education Sector Project : Tailoring International Best Practices to Improve Educational Outcomes at the State Level - Delivery Case Study - Roshan, Sabrina; Lomme, Roland; Hima Moussa Dioula, Halimatou; Santibanez, Claudio; Adekola, Olatunde Adetoyese; Bain, Katherine A. (Washington, DC: World Bank, 2022)
This case study seeks to understand how the Lagos Eko Secondary Education Project (Eko Project) tailored international best practices to leverage impact through education sector reforms in Lagos State’s public secondary school system. These best practices include an intensive utilization of evidence-based policy making, the granting of autonomy to a variety of stakeholders together with the expectation of accountability for results, community participation, incentives for reform, support for public-private partnerships (PPPs), and adaptive implementation. Research methods focus on the Science of Delivery case study guidelines, drawing on semi-structured interviews and focus group discussions with key stakeholders to better understand the implementation process and analyze the causal mechanisms for results achieved. The case study highlights four key contributors to the Eko Project’s politically savvy, locally tailored and adaptive delivery approach: (i) it managed to build on collective leadership along the entire delivery chain, from the political leadership of the governor down to the professional leadership of classroom teachers; (ii) it bounced back from a setback in outcomes by strengthening data collection and analysis of results; (iii) it struck the right balance between external and internal implementation mechanisms to make the most of established institutions; and (iv) it aimed at macro-level impact by reaching down to individual learning achievements.